Strategi Komunikasi IKPB Yogyakarta dalam Meningkatkan Kepedulian Mahasiswa Belitung terhadap Kebudayaan Daerah - Theo Khairullah; Amali, Muhammad Thoyib (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to analyze the communication strategy implemented by the Ikatan Keluarga Pelajar Belitong (IKPB) Yogyakarta to foster overseas students' awareness of local culture, and to evaluate its effectiveness in protecting socio-cultural identity amid modernization. Using a qualitative case study approach, data were collected comprehensively through in-depth interviews, participant observation, and documentation of the board members and active members of IKPB Yogyakarta. The results show that IKPB Yogyakarta successfully implemented the four components of Effendy's communication strategy: (1) recognizing the target audience through inclusive psychosocial mapping; (2) combining modern digital media (Instagram, WhatsApp) with conventional face-to-face media (dormitories) as cultural incubators; (3) formulating messages using local language symbols and practical educational approaches; and (4) positioning the board members as credible communicators and role models (patrons). The impact of this study confirms that this community-based communication strategy is highly effective in transforming apathy into communal pride while simultaneously motivating students to take concrete action. These findings are expected to serve as a reference for communication models that other regional student organizations can apply to strengthen the preservation of cultural heritage in overseas environments.